Percutaneous endoscopic gastrostomy tube placement for end-stage palliation of malignant gastrointestinal obstructions - Anouar Teriaky; Jamie Gregor; Nilesh Chande (The Saudi Journal of Gastroenterology, 2012)
Background/Aim: Decompression of malignant gastrointestinal obstructions is an uncommon indication for percutaneous endoscopic gastrostomy (PEG) tubes. The purpose of this study is to determine the efficacy of venting PEG tubes in relieving nausea and vomiting and assessing complications associated with tube placement. Patients and Methods: This study is a retrospective chart review of patients with PEG tubes placed to decompress malignant gastrointestinal obstructions between January 2005 and September 2010 by the gastroenterology service at our institute. Patient demographics, symptom relief, procedural complications, diet tolerability and home palliation were reviewed. Results: Seven PEG tubes were inserted to decompress malignant gastrointestinal obstructions. The mean patient age was 62 years (range 37-82 years). The underlying primary malignancies were small intestine (1), appendiceal (1), pancreatic (2), and colon (3) cancer. Gastric outlet obstruction was present in 3 (43%) patients while small bowel obstruction occurred in 4 (57%) patients. There was relief of nausea and vomiting in 6 (86%) patients. Procedural complications were present in 1 (14%) patient and involved superficial cellulitis followed by peristomal leakage. Patients with gastric outlet obstruction continued to have limited oral intake while patients with small bowel obstruction tolerated varying degrees of oral nutrition. Six (86%) patients were discharged home after PEG tube placement, but only 2 (33%) were able to undergo end-stage palliation at home without re-admission for hospital palliation. Conclusions: Venting PEG tubes significantly reduce the symptoms of nausea and vomiting in patients with metastatic gastrointestinal obstruction due to primary gastrointestinal malignancies. Complications associated with tube placement were minimal.